Comparison of Mobile Marketing Tools Used by Higher Education Institutions in Poland and Ukraine - Artur KISIOLEK; Oleh KARYY; Lіubov HALKIV (Communications of International Proceedings, 2020)
The need for marketing tools integrated into interactive communications with users of the global web-based hypermedia system led to the emergence of mobile marketing. The advantages of such communications and upward trends in the wireless telecom industry have resulted in the spread of mobile marketing. To find out how its tools are used in the higher education sector, a survey was conducted among the marketing representatives of Polish and Ukrainian higher education institutions. The authors studied the availability of mobile marketing resources in such institutions to prove the relationship between their mobile and desktop websites and to define the most (and least) common mobile marketing tools in this sector. The study was expected to show no significant differences between Polish and Ukrainian input regarding mobile marketing in higher education and confirm that a website adapted to mobile users in terms of marketing services supports achieving the site’s goals.
Keywords: Higher Education Institution; Educational Marketing; Comparative Analysis; Mobile Marketing.